OPTIMASI MIX PRODUKSI TOKO ROTI CHEN BAKERY DENGAN MENGGUNAKAN METODE LINEAR PROGRAMMING BERBASIS LINGO - Muhammad Naufal Farras; Sisca Octarina; Fitri Maya Puspita (Jurnal Komputer Terapan, 2026)
Small and Medium Enterprises (SMEs), like "Chen Bakery," often struggle with figuring out the best way to plan their daily production to make the most profit. There is a gap in research because not enough use mathematical models and computer tools to help with these decisions. This study tries to help "Chen Bakery" make more money each day by finding the best amounts to produce four main products—Sweet Bread, Sugar Donut, Mini Pizza, and Chocolate Pull-Apart Bread—while taking into account how much of the main ingredients they have and how much space is available in the oven. The method used is called Linear Programming, and it was set up and solved using LINGO 20.0 software. The results show that by planning production better, the bakery can make 24.7% more profit than it does now. LINGO software works well to find the best solutions and also helps understand how changes might affect the results, making it a useful tool for small business owners.